E-Books in Improving Knowledge, Attitudes and Behavior about the Dangers of Smoking - Fauzia, Malianawati; Widodorini, Trining; Handayani Lodra, Ester (Universitas Pendidikan Ganesha, 2025)
The prevalence of smoking among adolescents in Indonesia, especially in Malang, is still quite high, with many adolescents starting to smoke at a young age. Low knowledge about the dangers of smoking is one of the factors that encourage smoking behavior among adolescents. This study aims to evaluate the effectiveness of using e-books as an educational medium in increasing students' knowledge about the dangers of smoking. This study used a quasi-experimental design with a pretest-posttest approach. The study sample consisted of 41 students of SMP Muhammadiyah 1 Malang who were selected using a purposive sampling technique. Data were collected through questionnaires before and after the intervention in the form of providing an e-book entitled